Exposure to Early Life Adversity and Interpersonal Functioning in Attempted Suicide - Rajalin, Mia; Hirvikoski, Tatja; Renberg, Ellinor Salander; Åsberg, Marie; Jokinen, Jussi (Frontiers in Psychiatry, 2020)
Background Early life adversity (ELA) may lead to an increased risk for mental health problems including suicidal behavior. ELA alters biological stress systems that affect behavior and control within the individual that in turn will affect interpersonal behavior. Strained relations and interpersonal conflicts leading to rejection and isolation have been shown to be factors for suicidal behavior. Difficulties in interpersonal relationships are a common reason for seeking help in psychiatric care. In the present study, we examined relationship between different types of interpersonal problems and adverse childhood experiences in patients with a recent suicide attempt. Method The study included 181 recent suicide attempters. We assessed early life adversity and specific interpersonal problems by using the Karolinska Interpersonal Violence Scale and the Inventory of Interpersonal problems respectively. Results Suicide attempters with high levels of early life adversity expressed a more socially avoidant, non-assertive, and exploitable personal style even after adjustment for comorbidities with personality disorder and substance use disorder. Conclusions Patients with a recent suicide attempt with high levels of early life adversity tend to isolate themselves, of being introvert, and having difficulties to open up and confide in others. They report low self-confidence and self-esteem and problems with feeling and expressing anger. These behaviors complicate interaction with others and make establishment of solid relationships more difficult. In regards to detection of suicidal communication and treatment of suicidal patients, this may lead to misinterpretations and difficulties to fully benefit from treatment given or for professionals to provide the appropriate treatment. Clinicians should closely investigate the presence of early life adversity in suicidal patients and pay attention to their personal style and their difficulties in interpersonal exchange.